Bacillus subtilis spores as vaccine adjuvants: further insights into the mechanisms of action. - Renata Damásio de Souza (Public Library of Science (PLoS), 2014)
Bacillus subtilis spores have received growing attention regarding potential biotechnological applications, including the use as probiotics and in vaccine formulations. B. subtilis spores have also been shown to behave as particulate vaccine adjuvants, promoting the increase of antibody responses after co-administration with antigens either admixed or adsorbed on the spore surface. In this study, we further evaluated the immune modulatory properties of B. subtilis spores using a recombinant HIV gag p24 protein as a model antigen. The adjuvant effects of B. subtilis spores were not affected by the genetic background of the mouse lineage and did not induce significant inflammatory or deleterious effects after parenteral administration. Our results demonstrated that co-administration, but not adsorption to the spore surface, enhanced the immunogenicity of that target antigen after subcutaneous administration to BALB/c and C57BL/6 mice. Spores promoted activation of antigen presenting cells as demonstrated by the upregulation of MHC and CD40 molecules and enhanced secretion of pro-inflammatory cytokines by murine dendritic cells. In addition, in vivo studies indicated a direct role of the innate immunity on the immunomodulatory properties of B. subtilis spores, as demonstrated by the lack of adjuvant effects on MyD88 and TLR2 knockout mouse strains.